Diagnostics and treatment of ADHD in Switzerland : a physician perspective on practice and challenges - Frank Wieber; Hotz, Sandra; Kurt Albermann; Julia Dratva; Michael von Rhein (My University, 2018)
Background: Attention deficit/hyperactivity disorder (ADHD) is a major public health problem with numerous negative outcomes for the affected individuals and with a high burden to families and society. Although a multimodal therapeutic approach (i.e., pharmacological treatment as well as non-pharmaceutical treatment options) is considered the gold standard, the observed increasing methylphenidate (MPH) treatment could correspond to a reduced use of other treatments options. This study therefore aims to providing insights into the actual practice of paediatricians as well as perceived challenges during the diagnosis and treatment. Methods: An online survey on diagnostic and therapy procedures, personal attitudes, and perceived challenges regarding ADHD was sent to the members of the Swiss Society for Paediatrics. With 151 questionnaires that were analyzed, response rate was low (7%). Results: Paediatricians reported the exchange with parents and children as well as the suffering of the children to be central when selecting a therapy. On average, they arrange three meetings with parents, of which two take place with the concerned child. They also report including information from several sources before arriving at a diagnosis. Pharmacological therapy was most frequent, followed by psychotherapy, and occupational therapy. Challenges mentioned were: the subjective character of the diagnosis and frequent co-morbidities, limited resources for case management, limited availability of child and youth psychiatry and psychotherapy, and unfavorable public attitudes toward medication. Conclusions: Paediatricians do consider a multimodal approach when treating ADHD and show a high involvement of family and child in the choice of therapy. However, they highlight the potential of improving the cooperation with other specialists, such as teachers and school social workers, and of improving the availability of psychotherapy and information on ADHD. Key messages: Paediatricians are in close exchange with parents and children and consider several (non-) pharmacological ADHD treatment options. Challenges comprise the interprofessional cooperation and coordination as well as the availability of psychotherapy and information on ADHD.
Keywords: attention-deficit/hyperactivity disorder; diagnosis; adult attention deficit hyperactivity disorder